Satisfaction of Patients from the Quality Service of Diagnosis of Health Problem in Public Health Institutions of Nepal - Gurung, Milan; Saraswat, Arvind (Nepal Journal of Multidisciplinary Research, 2019)
Health should be the first priority of each people; people can do creative work if s/he is healthy. According to the annual report of the Department of Health Services (DoHS) for fiscal year 2072/73 (2015/2016), the main institutions that delivered basic health services were 104 public hospitals, 303 private hospitals, 202 primary health care centres (PHCCs) and 3,803 health posts. The primary health care services also provided 12,660 primary health care outreach clinic (PHCORC) sites. The health service was affected from the earthquake of April 2015 so the study aims to identify the satisfaction of patient from quality of diagnosis of health problem in public health institutions after earthquake. The study had covered 82 health institutions (45 from Kavre and 37 from Sindhupalchowak district). The statistical result of t-test shows that there was significant difference in approach of doctors (p = .012), and counselling of doctors (p=.043) but there was no difference in answering the queries promptly (p=.187), and explanation given for aliment (p = .180). The descriptive data show slight increase in level of satisfaction of patient after earthquake. Still health posts established in rural setting have inadequate human resource basically doctors are not adequate so Government should provide the trained Doctor in rural areas to increase the access of rural people in health services.